Pemanfaatan Limbah Tempurung Kelapa Menjadi Briket Arang yang Bernilai Ekonomis Bagi Masyarakat Kelurahan Harapan Tani Kecamatan Kempas Indragiri Hilir - Sri Djuniati; Heltina, Desi; Meldha, Zuqni; ‘Audah, Safridatul; Hidayat, Wahyu; M. Nanda Dwi Putra; Fajri Aziz, Lutvhi; Jailani, M. Fariz; Butar-Butar, Wahyu Tri Efendi (Universitas Medan Area, 2025)
Indragiri Hilir is one of regency in Riau Province which have the most coconut plantations. Increasing of coconut production will be in line with the waste produced. The utilization of waste from coconut plantations, especially coconut shells, has not been carried out optimally in Harapan Tani Village, Kempas District, in Indragiri Hilir Regency. This is due to the lack of knowledge about the utilization of waste from coconut shells. In fact, if the waste is processed, it can become a product with high economic value, namely charcoal briquettes. So an efforts to increase public knowledge is needed to be carried out through community service activities, namely by socializing and training to produce charcoal briquettes from coconut shell waste. From the activities that have been carried out, there is a high interest from participants in participating in the training and there is an increase in participant knowledge of the benefits of coconut shell waste charcoal briquettes and participants are able to make briquettes from coconut shells independently.